The impact of an intervention taught by trained teachers on childhood overweight - Rosário, Rafaela (2012)
The purpose of this study was to assess the effects of a six-months’ nutrition program, delivered and taught by classroom teachers with in-service nutrition training, on the prevention of overweight and obesity among children in grades 1 to 4. In this randomized trial, four hundred and sixty four children from seven elementary schools were allocated to a nutrition educational program delivered by their own teachers. Intervened teachers had 12 sessions of three hours each with the researchers throughout six months, according to the topics nutrition and healthy eating, the importance of drinking water and healthy cooking activities. After each session, teachers were encouraged to develop activities in class focused on the learned topics. Sociodemographic, anthropometric, dietary, and physical activity assessments were performed at baseline and at the end of the intervention. In the intervention group the increase in Body Mass Index (BMI) z-score was significantly lower than in the control group (p = 0.009); fewer proportion of children became overweight in the intervened group compared with the control (5.6% vs. 18.4%; p = 0.037). Our study provides further support to decrease the overweight epidemic, involving classroom teachers in a training program and making them dedicated interventionists.